The Influence of Personal Health Data on the Health Coaching Process - Rutjes, Heleen; Willemsen, Martijn C.; Feijt, Milou A.; IJsselsteijn, Wijnand A. (Frontiers in Big Data, 2022)
Tracking health data, for example through wearable devices or health apps, is increasingly commonplace. Consequently, health coaches (e.g., personal trainers, dieticians) are facing growing numbers of clients who bring their data to the clinic. These data potentially add value to the coaching process, for example by showing more objective and specific information on clients’ behaviors. However, in practice, it turns out to be hard to effectively utilize health data in a coaching setting, and it is not yet fully understood how data affect the coaching process and the coach-client communication. We organized a workshop (12 coaches, 3 clients) and a field study (5 coaches, 6 clients), where we observed coach-client interactions enriched with data. By including both familiar and unfamiliar coach-client pairs, as well as alternating the timing of the data presented (i.e., at the beginning, or halfway through the session), we acquired a variety of data-driven coaching interactions and analyzed this using a mixture of qualitative and quantitative methods. Our results show that data are not ‘plug-and-play’. There is an extensive process of interpreting and contextualizing data, in which the client has a key role, that is essential to gain relevant and actionable insights from the data useful to the coaching process. We also observe that data affects the coach-client communication on both content and relationship levels. We will reflect on these insights in terms of design recommendations for wearable tracking devices and e-health technology in order to effectively support health coaches and their interactions with their clients.